The Impact of Dexmedetomidine-loaded Nano-microsphere Combined with Percutaneous Acupoint Electrical Stimulation on the Postoperative Cognitive Function of Elderly Patients with Hip Fracture: Dexmedetomidine-loaded Nano-microsphere Combined with Percutaneous - Wang, Shigao; Wang, Ju; Yang, Jianping (Cellular and Molecular Biology, 2022)
To explore the impact of nano-microsphere loaded with dexmedetomidine (DEX) combined with percutaneous acupoint electrical stimulation on the postoperative cognitive function of elderly patients with hip fracture. The free base was prepared by the alkali precipitation method in this research, and then the drug was loaded into PLGA microspheres to construct the drug sustained-release system. The PLAG microspheres loaded with DEX (MS/DEX) were prepared by the O/W emulsion volatilization method and then Gel-(DEX-MS/BUP) suspension was obtained. A scanning electron microscope (SEM) was used to analyze the characterization of the prepared drug-loaded nano-microsphere, rheological analysis was performed on the copolymer solution, and in vivo release and degradation, experiments were carried out. Wistar rats were randomly divided into four groups (n=ten). After the sciatic nerve block model was established, the block time was observed after the injection of each sustained-release agent. The results showed that the gel-forming temperature of Gel and Gel-(DEX-MS/BUP) were 27.3°C and 26.3°C, respectively. Both MS/BUP and Gel-(DEX-MS/BUP) drugs could completely enter the blocking state. There was no loss of motor function in the rats after GEL-DEX. The clinical trials showed that Gel-(DEX-MS/BUP) system had good in situ and sustained release effects, and the analgesic effect of local anesthesia was significantly improved.